Abnormal Concept Problems in Modern Psychology (an Analytical Study of Islamic Psychological Studies) - Nabila Huringiin; Miftah Ahmad; Alifah Yasmin (Islam Transformatif : Journal of Islamic Studies, 2022)
This paper describes the difference between the concept of human and the concept of normal-abnormal human behavior according to the views of modern psychology and Islam. And its suitability with the basic discussion of human nature. Conceptual discussion is of special interest by researchers because of its urgency in psychological studies. This is based on the phenomenon of society being confused in setting normal and abnormal standards. The researcher uses qualitative research, so the data used by the researcher is descriptive and narrative data, not numbers. The primary data sources used in this research are primary books related to modern psychology, especially in the specification of normal and abnormal studies, while books on psychology are generally a source of support for the results of the analysis in this study. The main focus of discussion in this article is the problem of the concept of normal and abnormal in modern psychological studies. This article explains that the standard of normal and abnormal in the study of modern psychology is strongly influenced by Western relativism. This is contrary to the concept of Islamic psychology which explains the study of normal and abnormal in detail and absolute. Tulisan ini menguraikan perbedaan konsep manusia dan konsep perilaku normal-abnormal manusia menurut pandangan psikologi modern dan Islam. Serta kesesuaiannya dengan pembahasan tentang landasan hakikat manusia. Pembahasan konseptual menjadi sebuah ketertarikan sendiri oleh peneliti dikarenakan urgensinya dalam kajian psikologi. Hal ini berdasarkan fenomena masyarakat akan kerancuan sosial dalam penetapan standar normal dan abnormal. Peneliti menggunakan jenis penelitian kualitatif, maka data-data yang digunakan peneliti adalah data-data dalam bentuk deskriptif dan narasi bukan angka. Sumber data primer yang digunakan dalam penelitian ini adalah buku-buku primer terkait psikologi modern khususnya dalam spesifikasi kajian normal dan abnormal, sedangkan buku-buku kajian psikologi pada umumnya menjadi sumber penunjang hasil analisa dalam penelitian ini. Fokus pembahasan utama dalam artikel ini adalah problem konsep normal dan abnormal dalam kajian psikologi modern. Artikel ini menjelaskan bahwa standar normal dan abnormal dalam kajian psikologi modern banyak dipengaruhi oleh relativisme Barat. Hal ini bertentangan dengan konsep psikologi Islam yang menjelaskan kajian normal dan abnormal secara terperinci dan absolut.